2002
DOI: 10.1523/jneurosci.22-24-10580.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bursting in Leech Heart Interneurons: Cell-Autonomous and Network-Based Mechanisms

Abstract: Rhythmic activity within the heartbeat pattern generator of the medicinal leech is based on the alternating bursting of mutually inhibitory pairs of oscillator heart interneurons (half-center oscillators). Bicuculline methiodide has been shown to block mutual inhibition between these interneurons and to cause them to spike tonically while recorded intracellularly (Schmidt and Calabrese, 1992). Using extracellular recording techniques, we show here that oscillator and premotor heart interneurons continue to bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
255
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(278 citation statements)
references
References 45 publications
21
255
0
2
Order By: Relevance
“…However, the PK-elicited gastric mill rhythm appears more appropriately defined as a hybrid CPG because, although it still relies on the reciprocal inhibition between LG and Int1, it also requires the intrinsic oscillatory activity of the AB neuron. The leech heartbeat CPG can also operate in either a network-based or intrinsic oscillatory mode (Cymbalyuk et al, 2002). However, in this latter system, there is a switch in the intrinsic properties of the same set of CPG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, the PK-elicited gastric mill rhythm appears more appropriately defined as a hybrid CPG because, although it still relies on the reciprocal inhibition between LG and Int1, it also requires the intrinsic oscillatory activity of the AB neuron. The leech heartbeat CPG can also operate in either a network-based or intrinsic oscillatory mode (Cymbalyuk et al, 2002). However, in this latter system, there is a switch in the intrinsic properties of the same set of CPG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…On a technical note, it has been observed that the "regular" rhythms computed numerically for the original HCO model are close to limit cycles but do not appear to fully converge [4]. There is a lack of continued damping of variability in the period, ISIs, etc.…”
Section: Insight Into the Escape-release Mechanismmentioning
confidence: 99%
“…Previous studies of this HCO model and electrophysiological studies of the leech heartbeat have addressed fundamental questions about the mechanism of bursting [4,5,[13][14][15][16][17]. Regarding I h specifically, these questions can be summarized in terms of roles: R1: What role does I h have in the existence of a stable HCO rhythm?…”
Section: Leech Heartbeat Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The activity pattern of autonomously active neurons can range from autonomously spiking to weak, irregular spiking and to regular bursting. The variety of activity patterns is explained by the ion channel diversity and the balance between inward and outward currents, a topic that has received considerable attention in invertebrate neurons [28][29][30]. Within the respiratory network two types of inward currents are particularly important in conferring autonomous activity patterns including bursting [26].…”
Section: Cellular Mechanisms Of Bursting In the Respiratory Networkmentioning
confidence: 99%